Semantics Analysis on the Proverbs of Traditional Nias Wedding at Dahadano Gawu-Gawu Village, Gunungsitoli City - Zebua, Etikat Muliana; Waruwu, Yaredi; Harefa, Afore Tahir; Zebua, Elwin Piarawan (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Proverbs are one of the cultural heritages that contain noble values and traditional wisdom passed down from generation to generation. In the era of globalization, the younger generation, especially in Dahadanö Gawu-Gawu Village, Gunungsitoli City, tends to ignore proverbs spoken in traditional Nias wedding ceremonies, due to a lack of understanding of their meaning. This study aims to analyze the types of meanings contained in proverbs used in traditional Nias wedding ceremonies, to preserve and revitalize cultural values among the younger generation. This research uses a qualitative approach using semantic analysis. Data were collected through interviews with traditional leaders and relevant books, and then analyzed through the stages of data recognition, coding, reduction, interpretation, and representation. The researcher used Geoffrey Leech's semantic theory which classifies meaning into seven types: conceptual, connotative, social, affective, reflective, collocative, and thematic. A total of 40 proverbs were identified and categorized. The results show that the most dominant type of meaning is conceptual meaning (31%), followed by connotative (29%), social (12%), reflective (11%), affective (9%), collocative (4%), and thematic (4%). The findings show that proverbs are not only rich in literal meaning, but also rich in cultural, emotional, and social values. This study concludes that semantic analysis is an effective method to reveal the layered meanings in proverbs.